2015
DOI: 10.1186/s40405-015-0006-4
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Japanese version of the Gambling Related Cognitions Scale (GRCS-J)

Abstract: This study aimed to develop and test the Japanese version of the Gambling Related Cognitions Scale (GRCS-J) to investigate its reliability and validity for assessing gambling cognitions in a Japanese sample. Five hundred and thirty-six participants (351 male, 185 female; Mean age = 29.75 years) from a community sample living in Japan were included in the analyses. The results of a confirmatory factor analysis confirmed that a five-factor model was appropriate for the data (goodness of fit index = .87, comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Moreover, the hierarchical regression analysis revealed that the gambling expectancy is significantly associated with gambling symptoms. These results are consistent with earlier research showing that probable disordered gamblers were more likely to make irrational predictions of gambling outcomes and had more positive gambling expectancies [7, 29]. Because disordered gamblers are likely to possess cognitive distortions [8], the inclusion of gambling cognitive distortion is crucial in the treatment of gambling disorders [6].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, the hierarchical regression analysis revealed that the gambling expectancy is significantly associated with gambling symptoms. These results are consistent with earlier research showing that probable disordered gamblers were more likely to make irrational predictions of gambling outcomes and had more positive gambling expectancies [7, 29]. Because disordered gamblers are likely to possess cognitive distortions [8], the inclusion of gambling cognitive distortion is crucial in the treatment of gambling disorders [6].…”
Section: Discussionsupporting
confidence: 89%
“…Higher scores indicated a higher number of cognitive distortions. The GRCS-J has excellent internal consistency ( α = .94) and good convergent validity with the SOGS-J ( r = .61) [29]. In this study, the total scale demonstrated high internal consistency ( α = .97).…”
Section: Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…The GSAS is a valid tool as it shows a significant correlation (r = .51) with the pathological gambling adaptation version of the Yale-Brown Obsessive-Compulsive Scale (Pallanti, DeCaria, Grant, Urpe, & Hollander, 2005) and holds internal consistency (Cronbach's a = .869). In Japan, although measures of gambling-related variables have been developed, the concepts measured, have been limited to specific domains, such as gambling urges (Tanaka et al, 2017) and gambling related cognition (Yokomitsu, Takahashi, Kanazawa, & Sakano, 2015). Furthermore, the GSAS was developed for Koreans (Kim et al, 2005) and also applied to sexual symptoms (the Sexual Symptom Assessment Scale; Raymond, Lloyd, Miner, & Kim, 2007), suggesting that it is globally useful and adaptable to various related investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The GRCS has been found to be highly reliable (scale Cronbach’s α = 0.93, domain Cronbach’s α = 0.77–0.91) and criterion valid when tested against the South Oaks Gambling Screen (SOGS) ( Whelan, Meyers, & Steenbergh, 2007 ), a widely used instrument for assessing gambling-related behavior ( Lesieur & Blume, 1987 ; Stinchfield, 2002 ). Validated versions of the GRCS have been developed for Chinese ( Oei, Lin, & Raylu, 2007 ), Japanese ( Yokomitsu & Takahashi, 2015 ), Turkish ( Arcan & Karanci, 2013 ), French ( Grall-Bronnec et al., 2012 ), and Italian samples ( Donati, Ancona, Chiesi, & Primi, 2015 ; Iliceto et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%